Frictional characteristics of PVD coated mechanical seals against carbon under various classes of liquid lubricants. Issue 5 (8th August 2016) - Shankar, S.; Krishnakumar, P.
Abstract : Purpose: The purpose of this study was to investigate the frictional characteristics of the mechanical seals by using an efficient pairing by providing a suitable lubricant. Among all techniques and lubrication, deposition of solid lubricants on the sliding surface of the mechanical seal was found to be the most effective method to reduce frictional coefficient, frictional force and seal face temperature, thereby increasing the life time of mechanical seal. Design/methodology/approach: In this study, two coatings, diamond-like carbon (DLC) and tungsten carbide/carbon (WC/C), was deposited over the stationary high-carbon high-chromium steel ring paired with resin-impregnated carbon. Their frictional characteristics were studied under various classes of liquid lubricants such as organic liquids, synthetic oil, mineral oil and vegetable oils using an experimental approach. Further, among all classes of liquid lubricants, the one which showed better frictional characteristics was mixed with 0.5, 1 and 2 wt% of potential environmental friendly solid lubricant – boric acid powder. Findings: The high hardness and low surface roughness of DLC- and WC/C-coated seal with the lubricant of palm olein oil containing 1 wt% of boric acid powder contributed a hybrid tribofilm and resulted in low and stable friction coefficient in the range of 0.04-0.05 without any measurable wear. Originality/value: A pair involving stationary DLC- and WC/C-coated seal ring and resin-impregnated carbon seal rotating ring for the application of mechanical seal was suggested and its frictional characteristics were studied under various classes of lubricants.